Evaluation of the School of Library and Information Studies' academic advising based on the undergraduate students' perspectives - Daria, Kriezel Joy R.; Apolinario, Rhea Rowena U. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2012)
Academic advising in the college is a dynamic process that assists the youth into developing sound decisions that would positively affect their academic and life career. With the issues of multiple academic concentrations available for a Library and Information Science student and the decreasing number of enrollees and graduates in SLIS, the research has been conducted to evaluate the current system of academic advising in the college. The study aimed to find out whether the advising process is perceived effective or not by the undergraduate SLIS students for the 2nd semester of academic year 2011-2012. Specifically, the study determined the advising needs of the three groups of students - original, shiftees and transferees, and their levels of satisfaction. Also, the research identified the strengths and weaknesses of the current advising system. Recommendations were made available towards the end of the study.
The survey sampled 132 students where 81 (61%) returns were gathered. Based on the responses, it was revealed that students are satisfied with regards to the different aspects of advising, namely: (a) overall satisfaction; (b) accuracy of information provided; (c) adequacy of notice about important deadlines; (d) availability of advising when desired, and; (e) amount of time available during advising sessions.
Majority of the respondents found the discussion of career alternatives and possible SLIS track as their advising needs. The original students who entered SLIS as regular freshmen identified the discussion of career alternatives, which belongs to the Academic Majors and Courses (AMC) category, as their top advising need. Shiftees identified the following activities as their needs: 1) discussing career alternatives; 2) discussing possible SLIS track; and 3) discussing track or academic concentration requirements, all of which belong to the AMC category. Transferees share the same sets of needs as the shiftees' with the addition of 1) discussing job placement opportunities and 2) discussing internship or OJT opportunities, which are both from the Personal Development and Interpersonal Relationship (PDIR) category.
In the current SLIS advising system, these activities are majorly tackled: 1) selecting classes for the next semester; 2) signing registration forms; 3) discussing content of courses/classes; 4) evaluating academic progress, and 5) discussing possible SLIS track. It covers: 50% of the registration and class scheduling activities (RCS); 17% for academic majors and courses (AMC); 8% personal development and interpersonal relationship, and; 0% for both exploration of institutional policies (EIP) and teaching personal skills (TPS). The college's advising strengths are on the provision of RCS activities while the weaknesses are on the other categories.
In general, the SLIS undergraduate students are satisfied with how the advising in the college is handled. Students feel that the information provided to them are accurate, the notice on important deadlines is sufficient, the availability and length of the advising sessions are satisfactory. However, the percentages of dissatisfied transfer students for the overall satisfaction accuracy of information provided and adequacy of notice about important deadlines aspects are higher than the other group of students.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Counseling in higher education -- Philippines -- Quezon City; Faculty advisors -- Philippines -- Quezon City